DIABETES MELLITUS PREVENTION EDUCATION AND BLOOD SUGAR SCREENING AT JATIRAYA COMMUNITY HEALTH CENTER, KENDARI CITY - Yusran, Sartiah; Ekaputri, Rista; Widarni, Widarni; Listian, Ayu; Ningsih, Sri Ratna; Nirwidiarni, Hikma Sri; Rabbihim, Inda (PEDAMAS (PENGABDIAN KEPADA MASYARAKAT), 2025)
Diabetes Mellitus (DM) is one of the chronic diseases whose prevalence is increasing worldwide. Approximately 537 million adults worldwide live with diabetes, and this number is projected to rise to 643 million by 2030 if no effective preventive measures are taken. The objective of this Community Service Program (PKM) is to enhance public knowledge and attitudes toward Diabetes Mellitus (DM) and to conduct blood sugar level screenings among the community in the service area of the BLUD UPTD Jatiraya Kendari Health Center, Southeast Sulawesi. The methodology for implementing this Community Service Program (PKM) includes two main components: education and awareness-raising activities related to Diabetes Mellitus (DM) and health examinations in the form of blood sugar level measurements. The target audience for the activities is the local community in the service area of the Jatiraya Health Center, using purposive sampling to select 25 respondents. To measure the effectiveness of the educational activity, qualitative feedback was used through brief question-and-answer sessions before and after the educational activity. Health screenings were conducted using a glucometer. Based on the results of the PKM activities, which included health education and early detection of DM at the Jatiraya Health Center, it can be concluded that 25 participants successfully gained good knowledge about DM. From the blood sugar level measurements conducted, it was found that 4% of the participants were diagnosed with diabetes, and 28% were indicated as pre-diabetic.